First Aid Accident Application Using Microsoft Visual Basic 6.0 - Astri Fatma Sari; Sutarno, Skom.,MMSI (Jurnal Sistem Informasi, 2008)
This paper explains the First Aid Accident Application that aims to increase knowledge in society to take appropriate measures, to first aid and care yourself or family members or people around, at the time affected. For that, the author wants to display it in the form computerization, the author hopes that information more attractive. For that authors would like to display it in the form of computerization.Â Keywords : First Aid Application, Information, Visual Basic 6.0